Construction of a hollow structure in La0.9K0.1CoO3−δ nanofibers via grain size control by Sr substitution with an enhanced catalytic performance for soot removal. Issue 18 (16th August 2019) - Fang, Fan; Zhao, Peng; Feng, Nengjie; Chen, Chong; Li, Xue; Liu, Geng; Wan, Hui; Guan, Guofeng
Abstract : The hollow structure is formed by Sr 2+ doping in La0.9 K0.1 CoO3− δ nanofibers for decreasing the grain size, which can improve the contact efficiency of soot–catalyst–gas as well as the intrinsic activity, responsible for the enhancement in activity. Abstract : Perovskite-type La0.9 K0.1 CoO3− δ nanofibers were fabricated successfully using an electrospinning technique with calcination, based on the successful preparation of LaCoO3 nanofibers considering the enhancement in the activity by K +, which could facilitate oxygen species transfer and accelerate redox circulation. Furthermore, a hollow structure could provide more pathways for soot transportation and transmission of reaction gas (O2 and NO), improving the contact efficiency of soot–catalyst–gas and contributing to the enhancement in catalytic activity. However, the grain size increasing in the calcination has a great influence on the formation of the hollow structure. Thence, the introduction of some Sr 2+ in La0.9 K0.1 CoO3− δ nanofibers was taken into consideration to construct the hollow structure, by the inhibition of grain growth during heat treatment at a high temperature. Meanwhile, the Sr 2+ doping could further promote the catalytic activity. After comparison, an appropriate amount of Sr 2+ was introduced and the perovskite-type La0.63 Sr0.27 K0.1 CoO3− δ nanotubes were successfully prepared in this work as a result. Besides, some related catalysts were also prepared for comparison with the same method. These as-prepared catalysts were investigated by a series of characterization techniques. The activity evaluation of the catalysts was carried out through temperature programmed oxidation in 5% O2 and 2000 ppm NO, as well as in the presence of 6% H2 O. According to the activity data, La0.63 Sr0.27 K0.1 CoO3− δ nanotubes could be recognized as a high-performance catalyst for soot oxidation.